Beliefs About Children’s Emotions in Chile - Halberstadt, Amy G.; Oertwig, Dejah; Riquelme, Enrique H. (Frontiers in Psychology, 2020)
To learn more about Chilean emotional beliefs related to emotion development, 271 Mapuche and non-Mapuche parents and teachers in urban and rural settings reported their emotion beliefs using a questionnaire invariant in the Chilean context (Riquelme, Miranda, & Halberstadt, in press). Included are six beliefs previously found to resonate across three U.S. cultures (e.g., beliefs about the value and cost of certain emotions, control of emotion, knowledge of children’s emotion, manipulation of emotion, and emotional autonomy), and five others distinctive to the indigenous people of this region (e.g., value of being calm, controlling fear specifically, interpersonality of emotion, learning about emotion from adults, and regulation through nature). MANOVAs were conducted to examine these beliefs across culture (Mapuche, non-Mapuche), role (parent, teacher), and geographical location (rural, urban). For U.S.-derived beliefs, there were no main effects, although two interactions with culture by role and location were significant. For all five Mapuche-generated beliefs, there were significant main effects for culture, role, and location. Results highlight both similarities and differences in beliefs across cultures, roles, and geographical location. Implications for the Chilean context include the importance of non-Mapuche teachers’ sensitivity to the values and emotion-related beliefs of Mapuche families. Implications for the global context include an expanded view of emotion-related beliefs, including beliefs that children can control fear and be calm, that emotion-related values include attending to the needs of others, and that two ways of controlling emotion are through learning by listening to/watching elders, and by being in nature. Word count: 246